2021
DOI: 10.1007/s11356-021-13280-3
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural mulching and fungicides—impacts on fungal biomass, mycotoxin occurrence, and soil organic matter decomposition

Abstract: Plastic and straw coverage (PC and SC) are often combined with fungicide application but their influence on fungicide entry into soil and the resulting consequences for soil quality are still unknown. The objective of this study was to investigate the impact of PC and SC, combined with fungicide application, on soil residual concentrations of fungicides (fenhexamid, cyprodinil, and fludioxonil), soil fungal biomass, mycotoxin occurrence, and soil organic matter (SOM) decomposition, depending on soil depth (0–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 84 publications
(119 reference statements)
0
17
0
Order By: Relevance
“…For the remaining investigation period, five samplings were conducted in larger time intervals (≥ 6 months) on 25 April 2017 (T3), 9 October 2017 (T6), 3 May 2018 (T7), 11 October 2018 (T8), and 23 July 2019 (T9). In order to give a complete overview over the samplings conducted in the 3-year field study, two further samplings have to be mentioned here: They were conducted on 19 June (T4) and 18 July (T5) in 2017 after fungicide application to estimate the influence of both coverage types (plastic vs. straw) on fungicide residues in soil and their impact on mycotoxin occurrence, microbial biomass, and SOM decomposition (results described in Meyer et al (2021)). Besides coverage type, the agricultural practice was identical in both treatments: Subsurface drip irrigation (three emitters per meter) was applied from March until September each year depending on weather conditions for 3-4 h a day (7-11 L water per meter).…”
Section: Experimental Design and Soil Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…For the remaining investigation period, five samplings were conducted in larger time intervals (≥ 6 months) on 25 April 2017 (T3), 9 October 2017 (T6), 3 May 2018 (T7), 11 October 2018 (T8), and 23 July 2019 (T9). In order to give a complete overview over the samplings conducted in the 3-year field study, two further samplings have to be mentioned here: They were conducted on 19 June (T4) and 18 July (T5) in 2017 after fungicide application to estimate the influence of both coverage types (plastic vs. straw) on fungicide residues in soil and their impact on mycotoxin occurrence, microbial biomass, and SOM decomposition (results described in Meyer et al (2021)). Besides coverage type, the agricultural practice was identical in both treatments: Subsurface drip irrigation (three emitters per meter) was applied from March until September each year depending on weather conditions for 3-4 h a day (7-11 L water per meter).…”
Section: Experimental Design and Soil Samplingmentioning
confidence: 99%
“…At the beginning of the experiment (T0-T2), the MBC:MBN ratios indicated larger fungal fractions under bare soil compared to PC, which were attributed to aboveground biomass entry, promoting fungal growth (Meyer et al 2020). However, during the annual fungicide application (in flowering period), the soil under SC received larger fungicide loads than under PC, which reduced fungal growth or rather promoted bacterial growth under SC (Meyer et al 2021). The larger soil temperature under PC might have additionally favored fungal growth (Pietikåinen et al 2005;Drenovsky et al 2010).…”
Section: Influence Of Soil Coverage On Quality and Composition Of Soil Organic Mattermentioning
confidence: 99%
“…Additionally, plastic films offer a substantial mechanical barrier to the fungicide entry into soils [17], which is not the case in SM. Thus, the fungicide residual concentrations in SM soils are expected to be considerably higher compared to PM [18]. Anyhow, recent studies have shown that fungicides can reach the soil, even under the use of impervious plastic covers [17,18], leading for example to a decrease by ca.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the fungicide residual concentrations in SM soils are expected to be considerably higher compared to PM [18]. Anyhow, recent studies have shown that fungicides can reach the soil, even under the use of impervious plastic covers [17,18], leading for example to a decrease by ca. 60% of microbial biomass [18,19].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation